Incubation Period for Neuroinvasive Toscana Virus Infections - Lison Laroche; Frédéric Jourdain; Nazli Ayhan; Anne-Laure Bañuls; Rémi Charrel; Jorian Prudhomme (Emerging Infectious Diseases, 2021)
Toscana virus (TOSV) is an emerging pathogen in the Mediterranean area and is neuroinvasive in its most severe form. Basic knowledge on TOSV biology is limited. We conducted a systematic review on travel-related infections to estimate the TOSV incubation period. We estimated the incubation period at 12.1 days.